Features of the legal nature of a notary procedural representation in the system of representative relationship - Філик, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In this article investigate questions of the concepts and features of the notary procedure representation relations in representative relations system and the issues of relationships with other subjects of the representation.